2011
DOI: 10.1099/mic.0.049320-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth-dependent secretome of Candida utilis

Abstract: Recently, the food yeast Candida utilis has emerged as an excellent host for production of heterologous proteins. Since secretion of the recombinant product is advantageous for its purification, we characterized the secreted proteome of C. utilis. Cells were cultivated to the exponential or stationary growth phase, and the proteins in the medium were identified by MS. In parallel, a draft genome sequence of C. utilis strain DSM 2361 was determined by massively parallel sequencing. Comparisons of protein and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 52 publications
2
34
2
Order By: Relevance
“…To eliminate acetonitrile, all samples were evaporated using a Speedvac (Genevac, Ipswich, England), and the peptides were resolubilized in 20 l of 0.1% trifluoroacetic acid (TFA). The amount of peptides in all samples was determined using a NanoDrop ND-1000 (Isogen Life Science, IJsselstein, The Netherlands) at 205 nm as described before (14,16,41,42).…”
Section: Methodsmentioning
confidence: 99%
“…To eliminate acetonitrile, all samples were evaporated using a Speedvac (Genevac, Ipswich, England), and the peptides were resolubilized in 20 l of 0.1% trifluoroacetic acid (TFA). The amount of peptides in all samples was determined using a NanoDrop ND-1000 (Isogen Life Science, IJsselstein, The Netherlands) at 205 nm as described before (14,16,41,42).…”
Section: Methodsmentioning
confidence: 99%
“…Alignment of multiple sequence reads to an arbitrarily assigned C. jadinii genomic consensus sequence revealed 50 % of matches, consistent with a diploid genome for this yeast. On the other hand, mapping of C. utilis sequence reads (Buerth et al 2011) revealed broad SNP occurrence peaks at 33 and 66 % on the same C. jadinii consensus, which suggests for C. utilis a ploidy of 3; triploidy was additionally confirmed by FACS of nuclear stained cells (Rupp et al 2015). Triploidy and not tetraploidy of C. utilis is consistent with its inability to sporulate (Kurtzman and BasehoarPowers 2011).…”
Section: Introductionmentioning
confidence: 55%
“…Automated gene prediction indicated 6147 and 5689 ORFs in C. utilis and C. jadinii, respectively; 16 unique ORFs for C. utilis and 64 unique ORFs for C. jadinii may not only represent genuine genetic differences but may also reflect larger gap sizes in the reported C. utilis genome sequence. Phylogenetic tree analyses of orthologous genes revealed that both yeast species are not members of the CUG-clade comprising the species Candida albicans, Debaromyces hansenii, and Pichia stipitis (Tomita et al 2012), which was confirmed by verifying a CUG-encoded conserved leucine residue in the Inv1 protein (Buerth et al 2011). Until today, functional gene analyses to verify phenotypic traits experimentally have not been reported for either yeast.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations